Media Transformation on Malaikat Juga Tahu Short Story by Dewi Lestari into Short Movie - Rae Shella Tivani Mareta; Adi Setyowati (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2023)
Many literary works, such as novels and short stories, have been transformed into works in the form of audio-visual or film. This results in a dualism between enthusiasts of both types of works. Many enthusiasts of original works (novels) are disappointed with the results of the transfer of media to films. However, some people are satisfied with the transfer of the media, even preferring the film version to the original novel. A collection of short stories entitled Rectoverso by Dee Lestari which was transferred into a film has received a lot of praise. A collection of short stories and films are equally able to achieve the attention of the public. The two versions of Rectoverso's works have also received many awards national and international. Thus, this makes researchers interested in studying one of the short stories in Rectiverso entitled Malaikat Juga Tahu and a short film version with the same title. This research aims to find out the differences in the elements of the work of Malaikat Juga Tahu in the form of a short story and short film and to find out how the short story of Malaikat Juga Tahu is narrowed, elaborated and varied to be presented in a short film. This research used a qualitative method with the use of Pamusuk Eneste's ecranization theory as an analytical tool. The results of this research indicate changes in aspects of expansion, narrowing and variations of stories from short stories to short films. These changes were made to make the audience more immersed in the story by adding dramatic elements. In addition, the visualization element that is prioritized in the film version demands changes in the story version so that it is more acceptable to the audience.